SOME CRITICAL REMARKS ON THE PRINCIPLES OF SOCIAL RESPONSIBILITY IN HEALTHCARE: THE INTERCONNECTION BETWEEN LEGAL RESEARCH AND INTERNATIONAL LAW - Kristaps Zariņš; Emīls Georgs Siders (International Comparative Jurisprudence, 2024)
The implementation of the socially responsible and sustainable conduct of corporations has been widely researched; however, it has rarely been associated with the healthcare sector. Moreover, corporate social responsibility regarding hospitals has seldom been defined. The activities of hospitals have an undeniable impact on climate change, as hospitals emit huge amounts of CO2 and are responsible for the management of medical waste. However, hospitals play a crucial role in contributing to the UN’s Sustainable Development Goals, namely by ensuring healthy lives. Thus, they have an obligation to provide sustainable treatment for patients by implementing sustainability into their own activities and choosing suppliers that promote sustainability. This research article aims to define social responsibility or corporate social responsibility in the healthcare sector by connecting the definitions of social responsibility that arise from other articles with the objectives of corporate social responsibility that are incorporated into international legislation. The authors find that the definitions of social responsibility offered by other researchers are vague; therefore, it is necessary to consult international and EU legislation. Only by comparing several international legislative acts is it possible to deduce what constitutes the socially responsible conduct of a hospital.